(untitled) (International Journal of Engineering and Computer Science, 2013)
Recently supporting real-time video transmission services with diverse QoS constraints has become one of the essential requirements for wireless communications networks. Consequently, how to efficiently guarantee QoS for video broadcast attracts more and more research attention. However, the unstable wireless environments and the popular layer structured video signals impose a great deal of challenges in delay QoS provisionings. Due to the highly varying wireless channels, the deterministic delay QoS requirements are usually hard to guarantee. As a result, statistical delay QoS guarantees, in terms of effective bandwidth or capacity and queue-length-bound or delay-bound violation probabilities, have been proposed and demonstrated as the powerful way to characterize delay QoS provisioning for wireless traffics. Besides QOS, many energy-efficiency techniques for wireless networks can be found in the literature, which include lowerlayers adaptation, optimization and end-users applications specifically designed to save energy. Thus energy-efficiency is becoming a key factor for the successful deployment of wireless networks. The development and validation of mechanisms for energy- efficient video broadcasting require the measurement of the energy consumption needed for video transmission. This paper presents an optimal energy efficient video transmission for cooperative wireless networks.